Regeneration after fire in campo rupestre: Short- and long-term vegetation dynamics - Le Stradic, Soizig [UNESP]; Hernandez, Pauline; Fernandes, G.Wilson; Buisson, Elise (Elsevier, 2018)
The Cerrado (Brazilian savanna) is the second largest biome in Brazil, covering 22% of the country, and campo rupestre is one of the most biodiverse ecosystem. Campo rupestre are extremely old mountaintop tropical ecosystems, composed of a mosaic of herbaceous, shrubland and savanna vegetation, generally located above 900 m above sea level characterized by shallow, acidic and nutrient-poor soils. In the context of increased land-use changes, effective conservation and management projects appear necessary to guarantee the conservation of these ecosystems. Although fire is a natural disturbance in campo rupestre, the effects of fire on vegetation dynamics remain poorly understood. Our objective was to assess the effects of fire on vegetation recovery and plant composition on both the short- and long-term in the main herbaceous vegetation types: the sandy and stony grasslands. We monitored plant community composition before and after a wildfire in order to assess the short-term vegetation recovery. Diachronic analyses of grasslands burnt at various dates were used to understand the effects of fire on the long-term vegetation dynamics. Our results highlighted a rapid recovery of campo rupestre vegetation after wildfires, suggesting a high adaptation to fire of plant communities. We did not find a significant variation in species richness of sandy grasslands according to time after fire, whereas higher species richness was observed in the recently burnt stony grasslands. No change in plant composition of campo rupestre in response to fire was highlighted, probably due to the high heterogeneity of this ecosystem. After fire, biomass gradually increased over time in both vegetation types. High biomass accumulation could lead to stronger fires. Further studies are necessary to understand the relationship between biomass accumulation and fire intensity in campo rupestre in order to set up adapted fire management strategies to conserve campo rupestre biodiversity.
Keywords: Biomass; Campo arenoso; Campo pedregoso; Rupestrian grasslands; Vegetation recovery; Wildfire